Impact of the Use of Agrochemicals and Organic Fertilizers in the Creating of Agrobiodiversity in the Aymara Communities of Puno - Apaza-Ticona, Jorge; Mamani-Flores, Adderly; Alanoca-Arocutipa, Vicente; Calderón-Torres, Alfredo; Flores-Mamani, Emilio; Inquilla-Mamani, Juan; Calatayud-Mendoza, Alfredo Pelayo (Journal of Ecohumanism, 2024)
The research is about the use of agrochemicals and organic fertilizers in the breeding of crops in the Aymara communities of Puno. The objective of the research is to describe and explain the practices and perceptions of farmers on the use of chemical and natural fertilizers in the production of various crops such as: tubers and grains, the characteristics of use and damage caused. For this, the qualitative-ethnographic methodology was used, with the help of techniques such as the interview, participant observation, theorical and practical experience and life stories, it allowed us to glimpse the context of the Aymara farmer. With the result of the research, a practice is perceived, that farmers combine agrochemical and natural fertilizers, in order to control pests and obtain better yields in production, they also show negative effects of the use of agrochemicals in production and human consumption, For this reason, some families are reoriented to invigorate in the communal and family organization on the traditional knowledge of the use of organic inputs in agriculture.